Analysis of H&M home supply chain and implementing such in Bangladeshi market of same arena - Oishi, Aynan Haque Ashrabee (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.